A SGLT2 Inhibitor Dapagliflozin Alleviates Diabetic Cardiomyopathy by Suppressing High Glucose-Induced Oxidative Stress in vivo and in vitro - Xing, Yu-jie; Liu, Biao-hu; Wan, Shu-jun; Cheng, Yi; Zhou, Si-min; Sun, Yue; Yao, Xin-ming; Hua, Qiang; Meng, Xiang-jian; Cheng, Jin-han; Zhong, Min; Zhang, Yan; et al. (Frontiers in Pharmacology, 2021)
Diabetic cardiomyopathy (DCM) is a serious complication of diabetes mellitus (DM). One of the hallmarks of the DCM is increased myocardium oxidative stress. The aim of this study was to explore the underlying mechanisms involved in the effects of dapagliflozin (Dap) on myocardial oxidative stress both in streptozotocin-induced DCM rats and H9C2 cells exposed to high glucose. In in vivo studies, diabetic rats were given Dap (1 mg/kg/day) by gavage for eight weeks. Dap treatment obviously ameliorated cardiac dysfunction, and improved myocardial fibrosis, apoptosis and oxidase stress. In in vitro studies, Dap also attenuated the increased levels of reactive oxygen species and cell death in H9C2 cells incubated with high glucose. Mechanically, Dap administration remarkably reduced the expression of membrane-bound nicotinamide dinucleotide phosphate (NADPH) oxidase subunits gp91phox and p22phox, suppressed the p67phox subunit translocation to membrane, and decreased the compensatory elevated copper, zinc superoxide dismutase (Cu/Zn-SOD) protein expression and total SOD activity both in vivo and in vitro. Collectively, our results indicated that Dap protects cardiac myocytes from damage caused by hyperglycemia through suppressing NADPH oxidase-mediated oxidative stress.